Modalities of protection of the rights of individuals according to the administrative-procedural order and in legal-administrative procedures - Horbalinskiy, V.; Markova, O. O.; Маркова, О. О.; Volkova, Yu.; Litoshko, V.; Hlukhoveria, K.; Olena Markova (Cuestiones Políticas. – 2023. – Vol. 41, № 78. – P. 94-103, 2023)
The object of the research was to consider the methods of protection of people’s rights according to the administrative-procedural order and also in administrative judicial proceedings. A number of normative legal acts regulating the use of tools for the protection of subjective public rights were considered. Attention has been drawn to the following methods of protection of people’s rights, according to the administrative-procedural order and in administrative judicial proceedings: administrative procedure; administrative mediation; administrative appeal; subjecting guilty public administration officials to special disciplinary liability; compensation for damage caused by unlawful actions (inaction) of public administration entities; means of self-defense and legal means of protest. The methodological basis of the research was presented as comparative-legal and systematic analysis, formal-legal method, method of interpretation, hermeneutic method, as well as methods of analysis and synthesis. It was concluded that in the scientific literature it is very often the case that protection methods are not used, but tools, means and forms. The authors also examine the methods of protection of rights, freedoms and interests of individuals in the sphere of public administration.

Метою дослідження було розглянути способи захисту прав громадян в адміністративно-процесуальному порядку, а також в адміністративному судочинстві. Розглянуто низку нормативно-правових актів, що регулюють застосування засобів захисту суб’єктивних публічних прав. Звернуто увагу на такі способи захисту прав громадян в адміністративно-процесуальному порядку та в адміністративному судочинстві: адміністративний порядок; адміністративне посередництво; адміністративне оскарження; притягнення винних посадових осіб державного управління до спеціальної дисциплінарної відповідальності; відшкодування шкоди, завданої неправомірними діями (бездіяльністю) суб'єктів державного управління; засоби самозахисту та законні засоби протесту. Методологічною основою дослідження були представлені порівняльно-правовий та системний аналіз, формально-юридичний метод, метод інтерпретації, герменевтичний метод, а також методи аналізу та синтезу. Зроблено висновок, що в науковій літературі дуже часто використовуються не методи захисту, а засоби, засоби та форми. Автори також досліджують способи захисту прав, свобод та інтересів особи у сфері державного управління.

Объектом исследования было рассмотрение способов защиты прав граждан в административно-процессуальном порядке, а также в административном судебном процессе.
Modalidades de protección de los derechos de las personas según el ordenamiento administrativo-procesal y en los procedimientos jurídico-administrativos
Keywords: publikatsii u WoS; Україна; administrative judicial procedure; methods of protection; model of administrative procedure; subjective rights; administrative-procedural order; адміністративне судочинство; способи захисту; модель адміністративного процесу; суб'єктивні права; адміністративно-процесуальний порядок; административный судебный процесс; Ukraine; способы защиты; модель административного процесса; субъективные права; административно-процессуальный порядок